2021
DOI: 10.2174/1871527319666200907123315
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Targeted Signaling Pathways in the Autism Spectrum Disorder: Implications for Early Detection and Targeted Therapy

Abstract: Background & Objective: Autism Spectrum Disorders (ASD) known as a neurodevelopmental disorder showing communication impairments and unusual patterns of behavior .It seems that ASD frequency is on the increase. Therefore, diagnostic tools that help detect the disease in the early stages can be very useful in better management of the disease. Recent studies represent that miRNAs as novel biomarkers can be used to find out the process and etiology of ASD by regulating various genes of multiple pathways. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Some researchers confirmed the downregulation of the genes Taar7h and Taar7b in the neuroactive ligand-receptor interaction pathway using gene expression characteristics analysis and weighted gene coexpression network analysis, demonstrating that Taars and related gene regulatory networks may play an important role in ASD [76]. Recent research indicates that the novel biomarker miRNA may influence the process and etiology of ASD by regulating different genes in a variety of ways, including neuroactive ligand-receptor interactions, serotonin synapses, and so on [77]. Serotonin, also known as serotonin (5-HT), is a critical neurotransmitter produced in intestinal chromaffin cells by TPH1 and is found in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 97%
“…Some researchers confirmed the downregulation of the genes Taar7h and Taar7b in the neuroactive ligand-receptor interaction pathway using gene expression characteristics analysis and weighted gene coexpression network analysis, demonstrating that Taars and related gene regulatory networks may play an important role in ASD [76]. Recent research indicates that the novel biomarker miRNA may influence the process and etiology of ASD by regulating different genes in a variety of ways, including neuroactive ligand-receptor interactions, serotonin synapses, and so on [77]. Serotonin, also known as serotonin (5-HT), is a critical neurotransmitter produced in intestinal chromaffin cells by TPH1 and is found in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 97%
“…Durankus demonstrated the beneficial effect of granulocyte colony-stimulating factor (G-CSF) in improving the core symptoms of ASD without serious side effects ( 33 ). Alizadeh reported that miRNAs might regulate targets of ASD-related pathways, such as neuroactive ligand-receptor interactions, 5-hydroxytryptaminergic synapses, calcium signaling, cAMP signaling, and PI3K-Akt signaling pathways ( 34 ). It is recognized that ASD is mediated by a combination of genetic and environmental factors, with the study showing that genetic factors lead to structural variations in the subcortical-cortical brain circuit regions in children with ASD and that environmental factors have a more significant impact on the development of gray matter thickness in the orbitofrontal cortex and anterior cingulate cortex in children with ASD ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, in the ASD field, there is no miRNA-based drug that has entered into clinical studies or been approved by the FDA yet. 136 However, several preclinical research studies demonstrated the efficacy and potential with the rapid development of ASD disease models. For example, a miR-1290 mimic can rescue the ASD phenotype in NSCs derived from idiopathic ASD patients.…”
Section: Mirna In Asd Therapymentioning
confidence: 99%